Examining the effects of the HIV‐1 protein Tat and morphine on antiretroviral accumulation and distribution within the brain - Austin M. Jones; Kara M. Rademeyer; Elias P. Rosen; Silas Contaifer; Dayanjan Wijesinghe; Kurt F. Hauser; MaryPeace McRae (Wiley, 2024)
Abstract Despite combination antiretroviral therapy effectively suppressing HIV within the periphery, neuro‐acquired HIV (neuroHIV) remains a significant problem and approximately half of people living with HIV will experience HIV‐associated neurocognitive disorders (HAND). Concurrent opioid use exacerbates neuroHIV by promoting neuroinflammation, neuronal injury and synaptodendritic culling, viral replication, and potentially altering antiretroviral concentrations within the brain. The present study examined the effects of HIV and morphine co‐exposure on the accumulation and spatial distribution of antiretroviral drugs across multiple regions within the brain in an HIV‐1 Tat transgenic mouse model by using infrared‐matrix‐assisted laser desorption electrospray ionization mass spectrometry imaging (IR‐MALDESI MSI). Morphine exposure uniquely decreased antiretroviral concentrations in anterior cerebral (primary motor and somatosensory) cortices, corpus collosum (anterior forceps), caudoputamen, nucleus accumbens, and posterior regions including the hippocampus, corpus callosum (main body), cerebral cortex (somatosensory and auditory cortices), thalamus, and hypothalamus. Interestingly, male mice experienced greater morphine‐associated decreases in antiretroviral concentrations than females. The study also assessed whether changes in antiretroviral concentrations were linked with inflammation in astroglia, assessed through the measurement of astroglial activation using glial fibrillary acidic protein (GFAP) as a marker. Alterations in antiretroviral concentrations co‐registering with areas of astroglial activation exhibited sex‐specific treatment differences. This study highlights the intricate interplay between HIV, opioids, and antiretroviral drugs within the CNS, elucidating distinct regional and sex variations in responsiveness. Our findings emphasize the identification of vulnerabilities within the neural landscape and underscore the necessity of carefully monitoring opioid use to maintain the efficacy of antiretroviral therapies.